A study on financial performance (Selected Liquidity Ratios & Management performance ratios) of BAG Films and Media Ltd - Sekar, Dr.S.; Saranya, Mrs.B. (International Journal of Scientific Research and Management (IJSRM), 2018)
Finance is the lifeblood of any business. The present study deals with the “Financial Performance Evaluation of BAG Films and Media Ltd”. It is necessary to evaluate the financial performance for further improvement in their strategies. As the title indicates, this is a study of the evaluation of financial performance of selected companies. The purpose of this study is to explain the actual accounting information and make analysis through different accounting techniques. In the present study, the Researcher has discussed the selected liquidity ratios & management ratios. Every possible effort has been made to examine the financial performance of the company.